Development of Ethnomathematical-Based Student Worksheets for Gordang Sambilan Musical Instruments on Cone Slice Material for Class XI SMA Primbana Medan - Nasution, Anggi Nadila Soraya; Irawan, Bambang; Rambe, Isnaini Halimah (Journal of Mathematics Technology and Education, 2021)
This study discusses the development of student worksheets based on the ethno mathematics of Gordang Sambilan musical instrument on the conic section material of class XI SMA Primbana Medan. This research is a development research that aims to determine the process of the development of the student worksheets based on the ethno mathematics of Gordang Sambilan musical instrument on the conic section material of class XI SMA Primbana Medan which is valid, practical, and effective. The research and the development model used in this study is the ADDIE model with 5 stages. The stages in the ADDIE model are: 1) Analysis; 2) Design; 3) Development; 4) Implementation; 5) Evaluation. The instrument used to measure the validity of the developed student worksheet was an assessment qustionnaire by two mathematics lecturers and one mathematics teacher, to measure the practicality of the instrument student worksheets which is used a student responses qustionnaire and to measure the effectiveness of the instrument student worksheets which is used a test of student learning outcomes after using student worksheets. The averages validity result for student worksheets is 4.36, which means that the developed student worksheets fulfill the valid criteria. The practicality based on the student responses questionnaires obtained an average score of 4.07, which means that the developed student worksheets fulfill the practical criteria. The effectiveness of the developed student worksheets based on the student learning outcomes test of class XI SMA Primbana Medan, the percentage of the completeness of the student learning outcomes test is 83.333% which means it is very effective.